Electrochemically induced sol–gel deposition of ZnO films on Pt-nanoparticle modified FTO surfaces for enhanced photoelectrocatalytic energy conversion. Issue 16 (17th February 2016) - Gutkowski, Ramona; Schuhmann, Wolfgang
Abstract : Integration of Pt-nanoparticles between ZnO used as a photo absorber and FTO results in higher IPCE values as compared to ZnO films deposited on unmodified FTO. Abstract : The low conductivity of transparent conductive oxides such as fluorine-doped tin oxides (FTO) has a high impact on the electrochemically induced deposition of semiconductor films for photoelectrocatalytic investigations. Furthermore, the often high recombination rate of photogenerated electron–hole pairs influences the photoelectrochemical performance of semiconductor films. In order to improve the semiconductor deposition process as well as to decrease electron–hole pair recombination, we propose modification of FTO by electrochemically induced deposition of Pt nanoparticles. The deposited Pt nanoparticles improve on the one hand the conductivity of the FTO and on the other hand they create nuclei at which the sol–gel semiconductor deposition starts. We use ZnO as a well-characterised material to evaluate the effect of the influencing parameters during electrochemically induced sol–gel deposition with respect to the incident photon-to-current efficiency (IPCE) derived from wavelength dependent photocurrent spectroscopy. Using optimised deposition parameters a substantially decreased recombination rate of photogenerated charge carriers is demonstrated, if Pt-nanoparticles are first deposited on the FTO surface. By improving the diffusion of photogenerated electrons to the Pt nanoparticles and hence to the back contact the photoelectrochemical performance of the deposited ZnO films is substantially increased.